MANAJEMEN RISIKO DAN KRISIS DALAM MENINGKATKAN KETAHANAN LEMBAGA PENDIDIKAN ISLAM: STUDI KAJIAN PADA MADRASAH IBTIDAIYAH SWASTA - Adesna; Oki Setiana Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Risk and crisis management are essential aspects in maintaining the sustainability and quality of Islamic educational institutions, particularly Private Islamic Elementary Schools (Madrasah Ibtidaiyah Swasta/MIS). This study aims to analyze the various risks faced by MIS, examine their potential impacts, and describe effective risk and crisis management strategies in the administration of Islamic educational institutions. The study employed a descriptive qualitative approach using a library research method. Data were collected from various sources, including academic books, scientific journals, educational regulations, and relevant documents on risk and crisis management in Islamic education. Data analysis was conducted through systematic processes of data reduction, categorization, interpretation, and conclusion drawing. The findings reveal that Private Islamic Elementary Schools face multiple risks, including strategic risks, operational risks, financial risks, human resource risks, reputational risks, and information technology risks. These risks have the potential to escalate into crises if not properly managed. Risk management is implemented through several stages, namely risk identification, risk analysis, risk evaluation, risk mitigation, and continuous monitoring and evaluation. Meanwhile, crisis management consists of three major phases: pre-crisis, crisis response, and post-crisis recovery. The success of risk and crisis management is significantly influenced by the leadership of the madrasa principal, stakeholder involvement, and the implementation of Islamic values such as amanah (trustworthiness), ikhtiar (effort), shura (consultation), and tawakkul (reliance on God). Therefore, risk and crisis management based on Islamic values serves as a strategic instrument for strengthening organizational resilience, maintaining educational quality, and ensuring the sustainability of Islamic educational institutions amidst the challenges of contemporary societal changes.